Extradural anesthesia with lidocaine combined with fentanyl or methadone to ovariohisterectomy in dogs - Diniz,Miriely Steim (2013)
PURPOSE: To compare the cardiopulmonary effects and the quality of anesthesia of the extradural lidocaine in combination with fentanyl or morphine in bitches undergoing ovariohysterectomy. METHODS: Sixteen female dogs, were sedated with intramuscular acepromazine (0.05mg kg-1), followed by anesthetic induction with intravenous propofol (4mg kg-1), to perform the lumbosacral puncture. The animals were randomly assigned to two treatments: T-F (n=8) extradural administration of fentanyl (5µg kg-1), T-M (n=8) extradural administration of methadone (0.3mg kg-1). In both treatment groups, opioids were combined with lidocaine, in order to make up a final volume of 0.4mL kg-1. Heart rate (HR), respiratory rate (RR), systolic arterial blood pressure (SABP), intra-operative anesthetic supplementation, blood gases and adverse effects were investigated. RESULTS: HR, arterial pH and blood gases did not differ between treatments at any time point. RR and SABP decreased after epidural anesthesia, but the values were in terms of the physiological range of dogs. Intra-operative anesthetic supplementation was required in 50% and 62.5% of the fentanyl and methadone treated dogs, respectively. CONCLUSION: The extradural lidocaine in combination with fentanyl or morphine allowed cardiopulmonary stability, however sufficient sensitive blockade was not provided in 100% of the dogs.